Biologiya ta‘limida talabalar ekologik madaniyatini shakllantirishda innovatsion metodlar - Yadgarova, S.K (SCIENCE and SOCIETY, 2023)
The article describes the organization of innovative processes, the content and essence of the concepts of "Innovative educational technologies" and "educational innovations", holding environmental days.
Keywords: innovations; innovative education; advanced pedagogical education; ecological education; ecological culture